2022
DOI: 10.1186/s12960-021-00668-y
|View full text |Cite
|
Sign up to set email alerts
|

Applying the workload indicators of staffing needs method in nursing health workforce planning: evidences from four hospitals in Vietnam

Abstract: Background Vietnam has encountered difficulties in ensuring an adequate and equitable distribution of health workforce. The traditional staffing norms stated in the Circular 08/TT-BYT issued in 2007 based solely on population or institutional size and do not adequately take into consideration the variations of need such as population density, mortality and morbidity patterns. To address this problem, more rigorous approaches are needed to determine the number of personnel in health facilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Human resources for health (HRH) are essential to successful health systems (Nair, Jawale, Dubey, Dharmadhikari, & Zadey, 2022). Using the WISN, health managers could analyze nurse workloads, determine staffing requirements, and effectively contribute to workforce planning (Nguyen, Phung, & Bui, 2022). The WISN approach can assist hospital management in tracking the workforce of healthcare providers, especially nurses.…”
Section: Resultsmentioning
confidence: 99%
“…Human resources for health (HRH) are essential to successful health systems (Nair, Jawale, Dubey, Dharmadhikari, & Zadey, 2022). Using the WISN, health managers could analyze nurse workloads, determine staffing requirements, and effectively contribute to workforce planning (Nguyen, Phung, & Bui, 2022). The WISN approach can assist hospital management in tracking the workforce of healthcare providers, especially nurses.…”
Section: Resultsmentioning
confidence: 99%
“…We did not have any difference in the hours worked among hospitals annually. Although Nguyen et al, reported a substantial difference in the hours worked by nurses between hospitals and between the departments of the same hospital in Vietnam [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of WISN allows manager health for analyze burden work nurse, counting need staff, and with thus by effective contribute to the planning process power work (Nguyen et al, 2022). Lack of fulfillment need source power man House sick give influence burden high work to power health and cause decline satisfaction to service patient, increase desire move work and decline quality safety patient (Nasution et al, 2020).…”
Section: Setting Standards Burden Workmentioning
confidence: 99%